Effects of Enhancing Perceived Self-Efficiency for Behavior in Prevention of Complications of Type 2 Diabetic Patients - Palapol, Thongmee; Srisarakhum, Pakinee; Srisarakhum, Ruttanaporn (Journal of The Royal Thai Army Nurses, 2022)
This research was a quasi-experimental design with pretest-posttest control groups. The objectives were to study the effect of enhancing perceived self-efficiency for behavior in prevention of complications of type 2 diabetic patients. The sample group comprised of 60 diabetic patients in a health promoting hospital Bandoo sub-district and in a health promoting hospital nongbua sub-district. The sample were selected by simple random sampling and divided into experimental and control groups with 30 samples in each. The research instruments included the enhancing perceived self-efficiency program, the demographic data form, behavior in prevention of complications of diabetic patients data form with the reliability of .71. Statistics used for data analysis included frequency, percentage, paired t-test, and independent t-test. The research results revealed that after the experiment, the experimental group had increased posttest behavior in prevention of complications score over their pretest behavior in prevention of complications score, and who were receiving enhancing perceived self-efficiency had higher score on perceived self-efficiency than the group who receiving only routine care with statistical significance .05.